Formation of the key performance indicators system for lean management of enterprises - Kolos, Irina (My University, 2018)
The object of research is the elements of the system of key performance indicators (KPI) in their interaction to assess the results of lean changes with a focus on stimulating lean transformations. According to the results of the modeling, critical analysis, logical generalization, the expediency of using lean production methods in the process of forming an integral KPI system and its further practical support is substantiated. According to the results of the application of 5W, methods of critical analysis and scientific information retrieval, the application of criteria for the selection of indicators to the KPI system is proposed: causativeness and causality between indicators and development goals in the current period and in the future; immanence of the indicator time lag to operational improvements and improved financial results; stimulating the direction of the indicator to lean transformation and significance; elimination of indicators with multicollinear links; exclusion of indicators, which create a conflict of interest. It has been proven that the combination of 5S+5W+Jidoka+Kaizen will strengthen the validity during the qualitative selection and the inclusion of a specific analytical indicator in the KPI system. Combining SOP+VSM+Visual Management+Kanban will ensure objectivity in the development of internal standards for assessment/analyzing the results and dynamics of lean changes. SMED contribute to the correctness of obtaining results in the process of practical implementation of the existing KPI system in the system of lean enterprise management. According to the results of a systematic and critical analysis, a logical generalization, the importance and feasibility of developing internal standards for assessing/analyzing the results and the dynamics of lean changes have been proved: Regulation on the organization of assessment/analysis of the results and dynamics of lean changes; Methods for assessing/analyzing a specific indicator; Album of unified forms of management reporting; Regulation on the automation of assessment/analysis in the information system. Their annotated content is proposed. This will provide an unambiguous understanding of the KPI system by all stakeholders, reducing the time to generate the required data set and perform calculations. As a result, the purposefulness of developing alternatives for making weighted management decisions with a focus on maintaining an acceptable level of lean transformations and the effectiveness of further development on the basis of lean.
Keywords: key performance indicators; internal standards of the enterprise; methods of lean production; ключові показники ефективності; внутрішні стандарти підприємства; методи ощадливого виробництва; кафедра обліку і аудиту